Enhancing Student Learning Outcomes Through Experiential Learning Practices: A Meta-Analysis - Alditia, Lalu Muhammad; Suhandi, Andi; Riyadi, Arie Rakhmat; Fadillah, Nurul (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
Implementing the experiential learning model is one effective step in improving student learning outcomes, but recent evidence regarding its effectiveness is still inconsistent and not widely reported. Therefore, to gain a deep understanding and identify the effectiveness of experiential learning practices, this meta-analysis review was conducted. This review was conducted on 23 studies with 40 effect sizes obtained from the Scopus, ERIC, and Web of Science databases. The analysis model used was a random effects model with a robust variance estimation (RVE) approach to address the issue of interdependence between effect sizes within a single study. The measurement results show a high overall effect size (Hedges's g = 1.15; 95% CI), indicating a significant positive impact. Heterogeneity estimates are very high (I² = 98.2%), requiring further moderator analysis. Meta-regression analysis of the variables of education level, treatment type, and learning outcome dimension showed that only the education level variable approached significance in moderating the variation in learning outcomes. Subgroup analysis showed variation in the effectiveness of intervention implementation within each moderator category, but all were within the positive range. Publication bias tests showed bias, but correction using the trim-and-fill method and Peter's test proved that these findings remained consistent and valid. Overall, experiential learning has proven effective in enhancing and shaping various dimensions of student learning outcomes. This approach has great potential to continue being used and integrated into future learning practices, especially through the support of various pedagogical innovations and technology integration.